Challenges in implementing system thinking in agricultural sustainable intensification: A methodological note - Wuletawu, Abera; Yonas, Getahah Sahile; Eshetae, Meron Awoke; Getachew, Tesfaye; Liben, Feyera; Tamene, Lulseged D. (2023)
System thinking is relevant to solve complex problems and deliver solutions for sustainable intensification of agricultural systems. Successful implementation of System Thinking in Sustainable Intensification of Agricultural Systems has faced conceptual hurdles that hinder its practical application. This methodological note addressed these challenges by emphasizing on the complexity and difficulty in conceptualizing STIBs and considering the absence of standardized approaches. These issues significantly impact the authentic integration of system thinking into agricultural systems. Key impediments include the identification of stakeholders and the determination of objective functions for STIBs implementation. Moreover, the spatial scale, spanning from the plot to the national level, poses a crucial consideration, as all issues across these scales contribute to effective system thinking. The temporal scale is equally important, encompassing events and phenomena over both short and extended periods. While efforts have been made to develop tools and approaches for guiding STIBs implementation within specific components or sectors, there is a notable gap in tools that facilitate a comprehensive system approach. Existing tools designed for this purpose are limited in their implementation and are not widely adopted. Alternatively, a critical approach involves selecting tools across scales and chaining them together to address these challenges. In this context, we designed an example of how tools at the plot, household (HH), landscape, and national scales can be strategically chained to tackle some of the aforementioned challenges, using Ethiopia as a case study. However, it is important to acknowledge the limitations associated with coupling and utilizing these processes effectively. By exploring the integration of tools across different scales and systematically chaining them, there is potential to overcome the current challenges in STIBs implementation. This methodological exploration aims to contribute to the development of a more holistic and widely applicable framework for successful system thinking in the context of sustainable agricultural intensification.